Development of semantic verbal fluency in children aged 2 to 5 and its relationship with participating in music activities - Ritva Torppa; Valerie Looi; Pentti Henttonen; Seija Pekkala (PLoS ONE, 2026)
This cross-sectional study investigates the development of semantic verbal fluency performance (i.e., verbal recall) and the role of music participation in 79 normally-hearing Finnish children aged 2;0–5;11. The primary outcome measure was a semantic verbal fluency task where children listed as many animals or clothes as they could in 60 seconds. Additionally, parents filled in the “Role of Music in Families” questionnaire detailing their child’s formal and informal music activities. Results showed that the number of correct words belonging to the given category, along with the number of semantic clusters, subcategories and switches between subcategories, increased significantly with age. The rate of development between age groups differed for different aspects of verbal fluency, and more informal music activities was associated with better performance. These results indicate maturation of verbal recall from age 2;00 onwards, and that informal music participation is associated with the rate of development.